The ecological safety rise of feed system of transport energy equipment - Sudnik V.K.; Melnichuk L.P.; Orlov V.V. (General Energy Institute of the National Academy of Sciences of Ukraine, 2001)
The features of gas fuel employment as means for reduction of harmful emissions by autotransport are considered. The feed system of transport energy equipment on the base of novel technique of initial fuel thermal decomposition before burning into engine. This technique allows to cardinal reduce the toxicity of exhaust gases, to increase the efficiency of motor fuel applications and to extend the raw for production.